Störenfriede im öffentlichen Interesse : Der Skulpturenweg Nordhorn als offenes Museum - Denk, Andreas; Dittberner, Hugo; Duden, Anne; Frohne, Ursula (Anna); Heubach, Friedrich Wolfram; Hoet, Jan; Katti, Christian; Köttering, Martin; Loers, Veit; Nachtigäller, Roland; Ronte, Dieter; Schmidt-Wulffen, Stephan; et al. (Nordhorn : Städtische Galerie Nordhorn, 1997)
Baumann, Herbert ; Bühl, Hede ; Buxel, Reinhard ; Damsté, Christiaan Paul ; Deacon, Richard ; Dodeigne, Eugène ; Fujiwara, Makoto ; Glossner, Wolf ; Graham, Dan ; Hauser, Erich ; Hawoli ; Herold, Georg ; Holzer, Jenny ; Jenssen, Olav Christopher ; Kubach-Wilmsen-Team ; de Locht, Peter van ; Luginbühl, Bernhard ; Möbus, Christiane ; Niebuhr, Louis ; Udo, Nils - ; Pabel, Rudi ; Peters, Ralf ; Prantl, Karl ; Rogge, Cornelius ; Rübsam, Peter ; Rückriem, Ulrich ; Schad, Robert ; Schoenholtz, Michael ; Ulrichs, Timm ; Visch, Henk
biog., ind. tent., gr. tent., bibliog. p. 241-277
chronologie v/d Skulpturenweg Nordhorn p. 278-281
Duits
Skulpturenweg Nordhorn, Städtische Galerie Nordhorn, 10.03. - 10.04.1994
boek